2007
DOI: 10.1007/s11033-007-9204-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two AFLP markers linked to bacterial wilt resistance in tomato and conversion to SCAR markers

Abstract: Tomato bacterial wilt (BW) incited by Ralstonia solanacearum is a constraint on tomato production in tropical, subtropical and humid regions of the world. In this paper, we present the results of a research aimed at the identification of PCR-based markers amplified fragment length polymorphism (AFLP) linked to the genes that confer resistance to tomato BW. To this purpose, bulked segregant analysis was applied to an F(2) population segregating for the BW resistant gene and derived from the pair-cross between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…In a recent study, molecular markers associated with BW resistance in a highly-resistant cultivar (T51A) were reported (Miao et al 2009). The BW resistance in T51A was conferred by two complementary, co-dominant genes, located on tomato chromosome 6.…”
Section: Bacterial Wiltmentioning
confidence: 99%
“…In a recent study, molecular markers associated with BW resistance in a highly-resistant cultivar (T51A) were reported (Miao et al 2009). The BW resistance in T51A was conferred by two complementary, co-dominant genes, located on tomato chromosome 6.…”
Section: Bacterial Wiltmentioning
confidence: 99%
“…Mapping studies have shown the involvement of generalist as well as strain-specific quantitative trait loci (QTLs) in S. lycopersicum Hawaii 7996 (Carmeille et al 2006;Mangin et al 1999;Thoquet et al 1996;Wang et al 2000). In addition, bulked segregant analysis has shown the presence of two incompletely dominant genes associated with resistance in tomato cultivar T51A (Miao et al 2009). In pepper, the inheritance of BW resistance in a double haploid population derived from the cross C. annuum var.…”
Section: Introductionmentioning
confidence: 99%
“…This method was also applied to identify molecular markers that associated with resistance to bacteria in tomato (Miao et al, 2009), and those associated to cytoplasmic male sterility in Brassica napus (Zeng et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…AFLP markers combined with Bulk Segregant Analysis (BSA) method have been widely used to discover marker closely associated with trait in many crops including Brassica napus (Zeng et al, 2009) and tomato (Miao et al, 2009). AFLP markers have been used for analysis of oil palm genome (Barcelos et al, 2002), date palm genome (Rhouma et al, 2007) as well as other crops such as Amorphophallus variabilis (Santosa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%